B Cells in Tumor Microenvironment Associated With The Clinical Benefit to Programmed Cell Death Protein-1 Blockade Therapy in Patients With Advanced Esophageal Squamous Cell Carcinoma - Guo, Jhe-Cyuan; Hsu, Chia-Lang; Huang, Yen-Lin; Lin, Chia-Chi; Huang, Ta-Chen; Wu, I-Chen; Lin, Chen-Yuan; Lien, Ming-Yu; Kuo, Hung-Yang; Cheng, Ann-Lii; Hsu, Chih-Hung (Frontiers in Oncology, 2022)
Background: B cells and B cell-related gene signatures in the tumor microenvironment (TME) are associated with the efficacy of anti-programmed cell death-1 (anti-PD-1) therapy in several cancer types, but not known for esophageal squamous cell carcinoma (ESCC). Patients and Methods: Patients with advanced ESCC receiving anti-PD-1/PD-L1-based therapy were retrospectively included. A targeted RNA profiling of 770 immune-related genes from archival ESCC tissues was performed. Differential immune-related pathways and the levels of infiltrating immune cells were estimated through Gene Set Enrichment Analysis and CIBERSORT, respectively. CD19 and CD138 expression were evaluated through immunohistochemistry (IHC). The markers evaluated were correlated with clinical benefit (CB; defined as either objective response or stable disease for ≥6 months) and survival. Results: A total of 64 patients were enrolled. The transcriptome analysis based on 25 patients revealed that B cell signature was significantly increased in patients with CB (P < .05) and correlated with a longer PFS (P = .032) and OS (P = .013). Multiple genes representative of B cells, B cell functions, and plasma cells were upregulated in patients with CB. On further analysis of B cell subtypes in patients with CB, increase of naïve B cells (P = .057) and plasma cells (P < .01) was found but not memory B cells (P = .27). The CD19 expression in tumor stroma, detected by IHC, was higher in patients with CB (P = .033). Conclusion: B cells in the TME were associated with CB in patients with advanced ESCC receiving anti-PD-1/PD-L1-based therapy.